THE INFLUENCE OF LOCAL POWERS IN THE FIRST ASTUR EXPANSION (9 TH AND 10 TH CENTURY). - Mínguez Fernández, José María (Revista de Historia Social y de las Mentalidades, 2024)
The swift Astur expansion between the  Cantabrian range and the Duero river is  explained in this article from the perspective  of the persistence of population and of some  kind of political organization, no matter how  rudimentary. The defense of this thesis is based  on the proven fact of an Astur occupation of  several settlements of the Duero plateau, which  had been in the more or less remote past centers  of social control or of military organization and  that, before their conquest, would turn to be the  seat of local powers with authority over small  districts and that had little or no articulation  between themselves. Deeply knowing the  territory and with government experience, they  would end up accepting the supremacy of Astur  kings. This acceptance would be rewarded  by their integration in the kingdom Ìs new  aristocracy alongside the old Astur aristocracy  and the ecclesiastical elite of bishops and abbots.
Keywords: Astur expansion; Local powers; Aristocracy 9th and 10th Century